The Criminal Liability of Spreading Fake News on Social Media in Indonesia - Santoso, Sinung Teguh; Tanuwijaya, Fannny; Suarda, I Gede Widhiana (Indonesian Journal of Law and Society, 2023)
The spread of fake news on social media raises many legal problems in Indonesia. These legal problems are mainly seen in the formulation of the law as well as in the law enforcement area. Legal problems related to the spread of fake news must be resolved at the level of legislation, policy, and law enforcement because it negatively impacts someone. In addition, studies on the spread of fake news in the Indonesian context are still overlooked. Therefore, reviewing the regulation on criminal liability for those who spread fake news on social media in Indonesia is very important. The doctrinal legal research methodology investigated three main issues discussed in this article. First, the current study shows that the act of spreading fake news on social media cannot be charged with Article 28 of the Indonesia Law Number 19 of 2016 concerning amendments to Law Number 8 of 2011 concerning Information and Electronic Transactions. Second, from several Indonesian court decisions studied, judges in deciding cases of spreading fake news on social media applied Law Number I of 1946 concerning Criminal Law. Lastly, related to criminal law reform, spreading fake news on social media should also be regulated by the Information and Electronic Transactions Laws.